Advances in global leadership. Vol. 7 - Mobley, William H.; Li, Ming; Wang, Ying (Emerald, 2012)
Volume 7 of "Advances in Global Leadership" includes timely and impactful chapters on various concepts and processes associated with leading across cultures and other boundaries. In these times of accelerating complexity and global inter-connectedness, a deeper understanding of the multiple contextual, organizational, and individual variables and processes associated effective international leadership is ever more important. This Volume, drawing on authors from many different cultures and contexts, contributes to bridging and integrating conceptual and practitioner perspectives in pursuing this deeper understanding.
Keywords: Leadership.; Executive ability.; International business enterprises -- Management.; elektronické knihy; electronic books